OPTIMIZATION OF ATHLETES’ TRAINING IN OLYMPIC AND PARALYMPIC SPORTS PREPARATION CENTERS THROUGH PSYCHOPHYSIOLOGICAL DIAGNOSTICS AND PSYCHOLOGICAL TESTING (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This study focuses on optimizing the training of athletes in Olympic and Paralympic sports preparation centers through psychophysiological diagnostics and psychological testing. It examines the assessment of athletes’ physical and psychological conditions, identification of their individual characteristics, and personalization of the training process. Analysis of psychological tests and physiological indicators helps determine stress resilience, attention focus, and motivational state of athletes. Based on the findings, recommendations are developed to optimize the training process, enhancing athletes’ potential for achieving high performance.